Artemisia Extract Suppresses NLRP3 and AIM2 Inflammasome Activation by Inhibition of ASC Phosphorylation - Su-Bin Kwak; Sushruta Koppula; Eun-Jung In; Xiao Sun; Young-Kyu Kim; Myong-Ki Kim; Kwang-Ho Lee; Tae-Bong Kang (Mediators of Inflammation)
Artemisia princeps var. orientalis (Asteraceae, A. princeps) is a well-known traditional medicinal herb used for treating various inflammatory disorders in Korea, Japan, China, and other Asian countries. In the present study, we investigated the effects of A. princeps extract (APO) on interleukin- (IL-) 1β regulation and inflammasome activation in bone marrow-derived macrophages (BMDMs) and monosodium urate- (MSU-) induced peritonitis mouse model in vivo. The APO treatment to BMDMs primed with lipopolysaccharide (LPS) attenuated the NLRP3 and AIM2 inflammasome activation induced by danger signals, such as ATP, nigericin, silica crystals, and poly (dA:dT), respectively. Mechanistic study revealed that APO suppressed the ASC oligomerization and speck formation, which are required for inflammasome activation. APO treatment also reduced the ASC phosphorylation induced by the combination of LPS and a tyrosine phosphatase inhibitor. In vivo evaluation revealed that intraperitoneal administration of APO reduced IL-1β levels, significantly (p<0.05) and dose dependently, in the MSU-induced peritonitis mouse model. In conclusion, our study is the first to report that the extract of A. princeps inhibits inflammasome activation through the modulation of ASC phosphorylation. Therefore, APO might be developed as therapeutic potential in the treatment of inflammasome-mediated inflammatory disorders, such as gouty arthritis.